Functional Characterization of Nupr1L, A Novel p53‐Regulated Isoform of the High‐Mobility Group (HMG)‐Related Protumoral Protein Nupr1. Issue 12 (24th August 2015) - Lopez, Maria Belen; Garcia, Maria Noé; Grasso, Daniel; Bintz, Jennifer; Molejon, Maria Inés; Velez, Gabriel; Lomberk, Gwen; Neira, Jose Luis; Urrutia, Raul; Iovanna, Juan
<x xml:space="preserve">Abstract</x> We have previously demonstrated a crucial role of nuclear protein 1 (NUPR1) in tumor development and progression. In this work, we report the functional characterization of a novel Nupr1‐like isoform (NUPR1L) and its functional interaction with the protumoral factor NUPR1. Through the use of primary sequence analysis, threading, and homology‐based molecular modeling, as well as expression and immunolocalization, studies reveal that NUPR1L displays properties, which are similar to member of the HMG‐like family of chromatin regulators, including its ability to translocate to the cell nucleus and bind to DNA. Analysis of the NUPR1L promoter showed the presence of two p53‐response elements at positions −37 and −7, respectively. Experiments using reporter assays combined with site‐directed mutagenesis and using cells with controllable p53 expression demonstrate that both of these sequences are responsible for the regulation of NUPR1L expression by p53. Congruently, NUPR1L gene expression is activated in response to DNA damage induced by oxaliplatin treatment or cell cycle arrest induced by serum starvation, two well‐validated methods to achieve p53 activation. Interestingly, expression of NUPR1L downregulates the expression of NUPR1, its closely related protumoral isoform, by a mechanism that involves the inhibition of its promoter activity. At the cellular level, overexpression of NUPR1L induces G1 cell cycle arrest and a decrease in their cell viability, an effect that is mediated, at least in part, by downregulating NUPR1 expression. Combined, these experiments constitute the first functional characterization of NUPR1L as a new p53‐induced gene, which negatively regulates the protumoral factor NUPR1. J. Cell. Physiol. 230: 2936–2950, 2015. © 2015 Wiley Periodicals, Inc.